Evolution of ubiquitous autonomous agents. (25th September 2009) - Hung, Jason C.; Chang, Han-Bin; Chang, Hsuan-Pu; Cheng, Yu-Hsin; , Kuo-Yen Lo
Ubiquitous researches had been done recently. With the development of cellular phones and internet, these individualised programs exist in the digital world where a new ecosystem can be formed. Competition and collaboration thus exists among different groups of autonomous entities. We propose a model like food web exists in natural world and serves as a balancing algorithm among different types of species. We define the food web model and propose algorithms for formation and communication. The proposed model can be used to consider the development of intelligent strategies and the underlying communication topology such that ubiquitous intelligences can be evolved on the digital food web.